2020
DOI: 10.1080/17452007.2019.1706439
|View full text |Cite
|
Sign up to set email alerts
|

BIM-based operational information requirements for asset owners

Abstract: Nowadays, the advancements of wearable consumer devices have become a predominant role in healthcare gadgets. There is always a demand to obtain robust recognition of heterogeneous human activities in complicated IoT environments. The knowledge attained using these recognition models will be then combined with healthcare applications. In this way, the paper proposed a novel deep learning framework to recognize heterogeneous human activities using multimodal sensor data. The proposed framework is composed of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…Recent studies suggested that owner information regarding BIM successes by other competitive companies in operation, maintenance, repair, and remodeling is lacking [53,54]. However, BIM is a new process that requires reengineering and reshaping the construction process deals with various challenges in each BIM implementation level.…”
Section: Challenges Of Bim Implementation In Building Projectsmentioning
confidence: 99%
“…Recent studies suggested that owner information regarding BIM successes by other competitive companies in operation, maintenance, repair, and remodeling is lacking [53,54]. However, BIM is a new process that requires reengineering and reshaping the construction process deals with various challenges in each BIM implementation level.…”
Section: Challenges Of Bim Implementation In Building Projectsmentioning
confidence: 99%
“…The Employer's Information Requirements (Exchange Information Requirement in [37]) with the investor's guidelines is an important document of the investment process [34,41,42]. Its proper preparation can avoid disappointment with the end result [49].…”
Section: Discussionmentioning
confidence: 99%
“…The correct formulation of the Employer's Information Requirements is difficult and complex [34,41,42]. The aim of our research is analysis of Employer's Information Requirements as based on selected large construction projects from Poland.…”
Section: Introductionmentioning
confidence: 99%
“…Second, while higher LOD-LOI models can convey more detailed information, they can also raise some related intellectual property issues, leading to questions about the ownership of the data. Industry best practices address these issues by relying on thoroughly developed BIM execution plans and exchange information requirements, including specified LOD-LOI transfer expectations and agreements, to mitigate potential risks associated with the ownership of the models [57][58][59][60].…”
Section: Back-built Digital Twinsmentioning
confidence: 99%